Optimizing Outcomes in Free Flap Breast Reconstruction in the Community Hospital Setting: A Stepwise Approach to DIEP/SIEA Flap Procedures with Banking a Hemiabdominal Flap - Okada, Alberto; Pereira, Diego Daniel; Montag, Eduardo; Portocarrero, Marcelo; Felício, Carlos; Arruda, Eduardo Gustavo; Fonseca, Alexandre; Gemperli, Rolf; Munhoz, Alexandre Mendonça (Journal of Reconstructive Microsurgery, 2017)
Background Free flap breast reconstruction is a conventional procedure in many countries; however, microvascular compromise remains a devastating outcome. Given the morbidity of total necrosis, optimizing free flap salvage stands out as an important area for research, especially among surgeons to overcome the learning curve period and in resource constrained scenario such as community hospitals. To ensure free deep inferior epigastric perforator (DIEP)/superficial inferior epigastric artery (SIEA) flap breast reconstruction, the authors present a technique involving raising a hemiabdominal flap as a free flap, and banking the remaining flap to be utilized if needed in a subsequent procedure.Methods A retrospective review was performed on all free flap breast reconstructions. In this period, 84 patients (mean age: 50.1 ± 8 years) were included.Results In this study, 65.5% patients underwent immediate reconstruction, and 51.2% received DIEP reconstruction; 9.52% patients were returned to the operating room, and salvage reconstruction using the banked flap was performed in all patients. No differences were observed regarding early complications and age, body mass index, American Society of Anesthesiologists status, diabetes, smoking history, chemotherapy, radiotherapy, and type of flap used (p > 0.05). Hypertension was significantly associated with early complications (p < 0.05). Donor-site complications were associated with RT (p < 0.05).Conclusion The banked flap is a reliable method for ensuring DIEP/SIEA flap survival and should be considered in higher risk reconstructions and community hospitals. We believe that the present technique can be a good addition to the arsenal of plastic surgeons dealing with free flap breast reconstructions in selected patients.
Keywords: breast reconstruction; microsurgery; outcome